2019
DOI: 10.1002/acr.23601
|View full text |Cite
|
Sign up to set email alerts
|

Brain Correlates of Continuous Pain in Rheumatoid Arthritis as Measured by Pulsed Arterial Spin Labeling

Abstract: Objective Central nervous system pathways involving pain modulation shape the pain experience in patients with chronic pain. The aims of this study were to understand the mechanisms underlying pain in patients with rheumatoid arthritis (RA) and to identify brain signals that may serve as imaging markers for developing targeted treatments for RA‐related pain. Methods Patients with RA and matched control subjects underwent functional magnetic resonance imaging, using pulsed arterial spin labeling. The imaging co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Specifically, we previously reported diminished dlPFC activation in the current cohort of patients with RA during 2.5-second painful joint stimulation, 43 whereas increased dlPFC activation has been observed during continuous (6 minutes) but less intense painful stimulation. 32 Speculatively, the latter may reflect a stable ongoing inhibition via opioid signalling in response to continuous but lower painful stimulation intensity. However, when enough pain intensity is reached, the dlPFC may temporarily deactivate to protect the inflamed joints and to avoid additional harm.…”
Section: The Prefrontal Cortex In Rheumatic Conditionsmentioning
confidence: 99%
“…Specifically, we previously reported diminished dlPFC activation in the current cohort of patients with RA during 2.5-second painful joint stimulation, 43 whereas increased dlPFC activation has been observed during continuous (6 minutes) but less intense painful stimulation. 32 Speculatively, the latter may reflect a stable ongoing inhibition via opioid signalling in response to continuous but lower painful stimulation intensity. However, when enough pain intensity is reached, the dlPFC may temporarily deactivate to protect the inflamed joints and to avoid additional harm.…”
Section: The Prefrontal Cortex In Rheumatic Conditionsmentioning
confidence: 99%
“…Arterial spin labeling examinations of clinical pain have become more popular in recent years. Studies of different painful conditions including inherited erythromelalgia, 79 osteoarthritis of the hand 35,40 and knee, 18 trigeminal neuralgia and temporomandibular disorder, 29,100 fibromyalgia, 81 migraine, including pediatric migraine, 15,33,39,101 interstitial cystitis/chronic pelvic pain, 22,92 chemotherapy-induced painful neuropathy, 64 postherpetic neuralgia, 54 spondylotic myelopathy, 106 painful diabetic polyneuropathy (DPN), 78 rheumatoid arthritis, 46 Gulf War Illness, 49 and complex regional pain syndrome 80 have been reported.…”
Section: Imaging Chronic Pain With Arterial Spin Labelingmentioning
confidence: 99%
“…Several studies have found underlying brain anomalies associated with chronic pain, including alterations in brain function, structure, chemistry, and cerebral perfusion ( Simons et al, 2014 ; Kregel et al, 2015 ; Kumbhare et al, 2017 ; Jung et al, 2019 ; Lee et al, 2019 ). Recent studies have reported that patients with TN have structural and functional brain alterations ( Obermann et al, 2013 ; Henssen et al, 2019 ; Yan et al, 2019 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%